Decision Support System for Recommendation of Competition Types for Elementary School/Islamic Elementary School/Equivalent Students Using the TOPSIS Method - Valentino Shidney Shidney; Fauzan Masykur; Dyah Mustikasari; Raveenthiran Vivekanantharasa (PT Mekar Research and Publishing, 2026)
The selection of students to participate in competitions at the elementary school/Islamic elementary school/equivalent level has been done manually and subjectively, potentially causing inaccuracies in determining the type of competition that suits the students' abilities. This study aims to develop a web-based Decision Support System (DSS) using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to recommend the right type of competition for elementary school/Islamic elementary school students in Parang District. This system was built using the PHP programming language and MySQL database, with four main criteria: academic grades (weighted 0.35), artistic grades (weighted 0.25), sports grades (weighted 0.20), and student interests (weighted 0.20). The system was developed using the waterfall method and testing was carried out using white box testing. The test results showed that the system was able to produce student rankings based on TOPSIS preference scores with a 100% accuracy rate compared to manual calculations. This system is expected to assist teachers in making decisions more objectively, systematically, and efficiently.